1999
DOI: 10.1063/1.479635
|View full text |Cite
|
Sign up to set email alerts
|

State-resolved collisional quenching of highly vibrationally excited pyridine by water: The role of strong electrostatic attraction in V→RT energy transfer

Abstract: We report experiments that investigate the influence of long-range attractive forces on collisional energy loss from highly vibrationally excited molecules. State-resolved studies of energy transfer from highly vibrationally excited pyridine (μ=2.2 D) to water (μ=1.8 D) in a low-pressure environment at 298 K have been performed using high-resolution transient absorption spectroscopy of water at λ≈2.7 μm. Pyridine in its ground electronic state with 37 900 cm−1 of vibrational energy was prepared by absorption o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…53,54 Supercol- lision dynamics were first characterized by Flynn and coworkers for the pyrazine(E):CO 2 system using transient IR absorption. 34,35 The Mullin group has investigated supercollision dynamics for a number of highly excited donor molecules (pyrazine, pyridine, alkylated pyridines, and azulene) with a range of bath molecules (CO 2 , H 2 O, HOD, and DCl) 42,43,45,46,[55][56][57][58] and investigated the energy dependence of supercollisions for pyrazine(E), pyridine(E), and azulene(E) with CO 2 . 40,41,44,59,60 Sevy and co-workers have studied the interplay of photodissociation dynamics with collisional deactivation for several donor molecules with CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…53,54 Supercol- lision dynamics were first characterized by Flynn and coworkers for the pyrazine(E):CO 2 system using transient IR absorption. 34,35 The Mullin group has investigated supercollision dynamics for a number of highly excited donor molecules (pyrazine, pyridine, alkylated pyridines, and azulene) with a range of bath molecules (CO 2 , H 2 O, HOD, and DCl) 42,43,45,46,[55][56][57][58] and investigated the energy dependence of supercollisions for pyrazine(E), pyridine(E), and azulene(E) with CO 2 . 40,41,44,59,60 Sevy and co-workers have studied the interplay of photodissociation dynamics with collisional deactivation for several donor molecules with CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we describe preliminary results on vibrationally excited pyrazine colliding with a different cold bath gas, CO; a more complete experimental paper is in preparation . Using similar teclmiques, Mullin and co-workers have studied pyrazine/CO 2 , , pyrazine/H 2 O, pyridine/CO 2 , and pyridine/H 2 O . They have paid particular attention to the dependence of the energy loss on the initial excitation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Each data set was fit to a Boltzmann distribution with a rotational temperature. The distribution of scattered water from pyridine-h 5 was measured to be T rot ) 890 ( 150 K. This result is slightly larger than, but within error of, our previous result of T rot ) 770 ( 80 K. 19 For collisions of water with pyridined 5 , the scattered H 2 O(000) has a rotational temperature of T rot ) 890 ( 90 K, which is similar to the result for pyridine-h 5 : H 2 O. Less rotational energy is imparted to the high-J states of water in collisions with pyridine-f 5 where the rotational temperature of scattered water is T rot ) 530 ( 55 K.…”
Section: Dynamics Of Scattered H 2 O(000)mentioning
confidence: 80%
“…19 A sensitive test of large-∆E collisions between vibrationally hot molecules and a 300 K bath is the nascent rotational temperature, T rot , of scattered bath molecules. Earlier studies on a series of pyridine-based donors have shown that T rot for scattered H 2 O(000) molecules (with E rot > 1000 cm -1 ) decreases systematically for donors that have larger size, more vibrational modes, and increased vibrational state density.…”
Section: Introductionmentioning
confidence: 99%